Anti-inflammatory Effect of Curcumin, Homotaurine, and Vitamin D3 on Human Vitreous in Patients With Diabetic Retinopathy - Filippelli, Mariaelena; Campagna, Giuseppe; Vito, Pasquale; Zotti, Tiziana; Ventre, Luca; Rinaldi, Michele; Bartollino, Silvia; dell'Omo, Roberto; Costagliola, Ciro (Frontiers in Neurology, 2021)
PurposeTo determine the levels of pro-inflammatory cytokines and soluble mediators (TNF-α, IL6,IL2,and PDGF-AB)in 28 vitreous biopsies taken from patients with proliferative diabetic retinopathy and treated with increasing doses of curcumin(0.5μM and 1μM),with or without homotaurine (100μM) and vitamin D3 (50nM). Materials/methods.ELISA tests were performed on the supernatants from 28 vitreous biopsies that were incubated with bioactive molecules at 37°C for 20 h.The concentration of the soluble mediators was calculated from a calibration curve and expressed in pg/ml.Shapiro-Wilk test was used to verify the normality of distribution of the residuals.Continuous variables among groups were compared using the General Linear Model (GLM).Homoscedasticity was verified using Levene and Brown-Forsythe tests.Post-hoc analysis was also performed with the Tukey test.A p≤0.05 was considered statistically significant. Results.The post-hoc analysis revealed statistically detectable changes in the concentrations of TNF-α, IL2,and PDGF-AB in response to the treatment with curcumin,homotaurine,and vitamin D3.Specifically,the p-values for between group comparisons are as follows:TNF-α:(untreated vs. curcumin 0.5μM +homotaurine 100μM +vitamin D3 50nM)p=0.008,(curcumin 0.5μM vs. curcumin 0.5μM+homotaurine 100μM +vitamin D3 50nM)p=0.0004,(curcumin 0.5μM vs. curcumin 1μM +homotaurine 100μM +vitamin D3 50nM)p=0.02,(curcumin 1μM vs. curcumin 0.5μM +homotaurine 100μM +vitamin D3 50nM) p=0.025,and (homotaurine 100μM +vitamin D3 50nM vs. curcumin 0.5μM +homotaurine 100μM +vitamin D3 50nM) p=0.009;IL2:(untreated vs. curcumin 0.5μM +homotaurine 100μM +vitamin D3 50nM) p=0.0023,and (curcumin 0.5μM vs. curcumin 0.5μM+homotaurine 100μM +vitamin D3 50nM) p=0.0028;PDGF-AB:(untreated vs. curcumin 0.5μM +homotaurine 100μM +vitamin D3 50nM) p=0.04,(untreated vs. curcumin 1μM + homotaurine 100μM +vitamin D3 50nM) p=0.0006,(curcumin 0.5μM vs. curcumin 1μM + homotaurine 100μM +vitamin D3 50nM) p=0.006,and (homotaurine 100μM +vitamin D3 50nM vs. curcumin 1μM +homotaurine 100μM +vitamin D3 50nM) p=0.022.IL6 levels were not significantly affected by any treatment. Conclusions.Pro-inflammatory cytokines are associated with inflammation and angiogenesis,although there is a discrete variability in the doses of the mediators investigated among the different vitreous samples.Curcumin, homotaurine,and vitamin D3 individually have a slightly appreciable anti-inflammatory effect.However,when used in combination,these substances are able to modify the average levels of the soluble mediators of inflammation and retinal damage.Multi-target treatment may provide a therapeutic strategy for diabetic retinopathy in the future. The trial was registered at clinical trials.gov as NCT04378972 on 06May2020 https://register.clinicaltrials.gov/prs/app/action/SelectProtocol?sid=S0009UI8&selectaction=Edit&uid=U0003RKC&ts=2&cx=dstm4o